Outcome analysis of childhood pilocytic astrocytomas: a retrospective study of 148 cases at a single institution. Issue 6 (9th September 2013) - Colin, C.; Padovani, L.; Chappé, C.; Mercurio, S.; Scavarda, D.; Loundou, A.; Frassineti, F.; André, N.; Bouvier, C.; Korshunov, A.; Lena, G.; Figarella‐Branger, D.
Abstract : Background: Pilocytic astrocytomas (PAs) are characterized by an excellent prognosis although several factors of adverse outcome have been reported. The mitogen‐activated protein kinase pathway plays a major role in their tumorigenesis. Aim: To report a series of 148 PAs in children to define clinicopathological and biological prognostic factors. Methods: Clinical data were collected from patient files and mail inquiry. Pathological specimens were centrally reviewed. The three major KIAA1549 : BRAF fusion subtypes were analysed by reverse transcription – polymerase chain reaction (RT‐PCR) in a subset of 47 frozen cases and by fluorescence in situ hybridization on formalin‐fixed paraffin‐embedded tissue in 23 cases. Tumour location, age at surgery, extent of surgical removal, histological subtype and KIAA1549 : BRAF fusion by RT‐PCR were searched for prognostic significance. Results: Pilomyxoid astrocytoma (PMA) and the hypothalamo‐chiasmatic (H/C) location were associated with a worse prognosis [ P  < 0.001 for overall survival (OS) and P  = 0.001 for progression‐free survival (PFS)]. Patients who underwent complete surgical excision had a better OS ( P  = 0.004) and a longer PFS ( P  < 0.001) than the others. Age was also a strong prognostic factor for OS but not for PFS. Infants (<1 year) and young children (<3 years) had a much worse outcome than the others ( P  < 0.001 and P  = 0.004 respectively). KIAA1549 : BRAF fusion status was not predictive of outcome. Conclusion: This study highlights the good prognostic factors of PAs but H/C PA remains a subgroup with dismal prognosis associated with young age, PMA variant and incomplete surgery. Search for KIAA1549 : BRAF fusion in tumours with PA pattern is recommended even though the prognostic impact is still unclear.